RISK FACTORS AND TREATMENT OUTCOME OF CHILDREN WITH HCV INFECTION - Khosa, Ghazi; Aziz, Muhammad Tariq; Suleman, Hassan; Hussain, Ibrar; Abu-Talib, Muhammad; Joya, Saima Jabeen (Journal of Ayub Medical College Abbottabad, 2021)
Background: Combination of pegylated interferon Î±-2a or Î±-2b has been considered to be the standard for treating HCV infection among children. Many new agents inhibiting HCV during various steps while replicating is under study around the world. This study was aimed to note the efficacy of sofosbuvir and ribavirin among children having HCV infection. Methods: This was an open label experimental trail done at Department of Gastroenterology, Children Hospital and The Institute of Child Health, Multan. The study duration was from July to December 2019. A total of 89 HCV treatment naÃ¯ve children aged 6-16 years of age, having HCV PCR as positive were enrolled. Sofosbuvir as 400 mg once a day along with ribavirin 10-15 mg per kg per day in the form of once or twice as divided doses were given in all the cases. After starting the treatment, along with side effects, rapid virological response (RVR) as PCR at 4 weeks, early virological response (EVR) at 12 weeks and post treatment 12 weeks HCV PCR as sustained virological response (SVR) was noted. Results: Out of a total of 89 children, there were 53 (59.6%) boys and 36 (40.4%) girls. Mean age was noted to be 12.42±2.57 years. Majority of the children, 72 (80.9%) had genotype 3 while genotype 1 was noted in 11 (12.4%) and un-typable in remaining 6 (6.7%). History of blood or blood products transfusion was seen to be the commonest mode of HCV transmission, found in 41 (46.1%) children, perinatal transmission in 20 (22.5%) and history of previous surgery in 9 (10.1%). rapid virological response was noted in 73 (83.1%) children, all 89 (100%) children achieved EVR whereas SVR was noted in 86 (96.7%). Headache was the commonest side effect, reported by 24 (27.0%) followed by nausea in 15 (16.9%). Conclusion: Regardless of the genotype, sofosbuvir and ribavirin combination therapy was noted to have excellent efficacy amongst children with HCV infection. History of blood and blood product transfusion was the commonest risk factor found.